Measures to Protect the Environment and Conserve Energy Taken by the United States and Japan - Toshi H. Arimura and Kazuyuki Iwata (My University, 2016)
Document reviews policy measures to deal with the environmental problems and energy conservation in Japan and the United tates by examining both countries' policies toward air pollution and advocating to implement similar policies in local cities in Asian countries.